The importance of practical activities in science teaching as a strategy in the learning process (Research, Society and Development, 2022)
Science teaching is of great importance in the educational sector, because it is through it that the individual acquires the scientific knowledge necessary for the understanding of his own life and the world around him. Thus, it is up to the teacher, as a mediator of the teaching-learning process, to propose activities that encourage the active participation of students, so that they feel motivated to learn. In this context, the present article aimed to carry out a bibliographic research on studies that demonstrate the importance of practical classes for the learning process in Science teaching. Therefore, it is a study with a qualitative approach, which sought to carry out a bibliographic research, through scientific articles and annals of scientific meetings. Among the studies, 10 works were selected that address the different conceptions of teachers and students about the importance of practical classes in Science Teaching and the difficulties that teachers face in the application of practical classes. In general, it was noticeable that practical activities are necessary for a better assimilation of theoretical content, however, it was evident that teachers need to always be in training so that innovative methodologies are well established, thus providing an excellent connection between theory and practice.